The shimmers in the night : a novel - Millet, Lydia, 1968- (Big Mouth House, 2012)
When Cara's brother, Jax, texts her from "smart kids boot camp" in Boston, Cara and her two best friends go to the rescue and discover the camp is a front for her missing mother's organization that is fighting a force out to destroy life on Earth.